The reverse logistics and national policy of solid waste: a challenges to the brazilian reality - Thode Filho, Sergio (2015)
This paper aims to present the problem experienced by large urban centers and Brazil as a whole, as the huge amount of waste generated and it ́s improper disposal. Pointing out that there was an increase in activities related to recycling, but considering the waste generation growth, the effective participation of these initiatives is still irrelevant. The article brought the role and evolution of reverse logistics practices and parallel implementation of the National Policy of Solid Waste (PNRS). This legislation that defines reverse logistics as the way that society and businesses will lead to proper disposal of solid waste, being relevant to note that the full effectiveness of the legislation (PNRS) depends on a chain of actors, technical planning and human and environmental resources for their achievement. The proposed study provided descriptions and analyzes based on information gathered through a qualitative methodology structured around the secondary sources reading technique. This work indicates an evolution in the use of reverse logistics and consequently the adaptation of the law 12,305 (PNRS), but concluded that such growth was not relevant towards the constant evolution of consumption and waste generation bythe Brazilian population. Leaving room for further studies on reverse logistics issues and PNRS are realized and new proposals arise, giving sequence to the current study.